Light grazing alleviates aeolian erosion–deposition effects on microbial communities in a semi-arid grassland - Mingming Cui; Biqi Bao; Yipu Wu; Nan Hui; Mai-He Li; Shiqiang Wan; Shijie Han; Feirong Ren; Junqiang Zheng (Ecological Processes, 2024)
Abstract Background Soil erosion affects the stability of terrestrial ecosystems and ecosystem services by directly or indirectly impacting the cycling of soil materials and energy and reducing the fertility of grassland soils. However, research on microbial adaptation to grazing and soil erosion is limited, particularly in relation to grassland ecosystem restoration. Here, we assess microbial communities subjected to simulated soil erosion and grazing in a semi-arid grassland of Inner Mongolia, China. Results No significant change was observed in soil variables. However, the structure of the soil microbial community underwent significant changes as a result of soil erosion and soil erosion plus grazing, leading to a significant increase in the relative abundance of Cyanobacteria (116.80% vs 116.38%). Wind erosion and deposition contributed to an increase in the network complexity of soil bacterial and fungal communities. However, much of this effect was alleviated by grazing. Simultaneously, aeolian processes and grazing regulate soil microbial community assembly, leading to inconsistent patterns of change in bacterial and fungal communities. Under wind erosion and deposition, the relative contribution of deterministic processes (4.44% vs 31.11%) in bacterial communities increased, while the relative contribution of stochastic processes (2.23% vs 20%) in fungal communities reduced. Grazing resulted in a decrease in the relative contribution of deterministic processes (8.89%) in the bacterial community and an increase in the relative contribution of stochastic processes (8.89%) in the fungal community. Conclusion This study presents a comprehensive investigation of the response of soil microbial communities to aeolian erosion–deposition and grazing in a semi-arid grassland. Our findings indicate that microbial communities in the semi-arid grassland show resistance to external disturbances and that light grazing mitigates the effects of aeolian erosion–deposition on microbial communities, which is essential for maintaining the stability and biodiversity of grassland ecosystems.